1992
DOI: 10.1063/1.463721
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental structures of vinyl fluoride and vinyl alcohol

Abstract: A new theoretical r0 structure for vinyl fluoride has been derived using ab initio molecular orbital procedures. In addition, new experimental r0 and rs structures have been obtained through a reanalysis of existing experimental microwave data. Significant discrepancies are found between the new theoretical (125.4°) and experimental (127.6°) r0 estimates of the CCHu angle involving the hydrogen atom geminal to the substituted center. This is attributed to the relative insensitivity of the experimental structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…level, can provide a more accurate estimate of the structure of this molecule than can microwave spectral results [42]. Similar calculations on vinyl bromide and vinyl chloride produce results in good agreement with experimentally derived structures (it is relatively more difficult to determine the vinyl fluoride structure experimentally because some atoms lie very close to its inertial axes) [43].…”
Section: Methodsmentioning
confidence: 68%
“…level, can provide a more accurate estimate of the structure of this molecule than can microwave spectral results [42]. Similar calculations on vinyl bromide and vinyl chloride produce results in good agreement with experimentally derived structures (it is relatively more difficult to determine the vinyl fluoride structure experimentally because some atoms lie very close to its inertial axes) [43].…”
Section: Methodsmentioning
confidence: 68%
“…The equilibrium OH bond length 407 dismissed the experimental r s structure [122]. We recalculated the structure at the CCSD(T) level of theory.…”
Section: Vinyl Alcoholmentioning
confidence: 99%
“…Another important illustration of the reliability of MP2‐optimized geometries can be found in a paper that deals with the structure of vinyl alcohol (Smith & Radom, 1990), where it has been shown that the previous disagreement between the ab initio r 0 structure and the r s obtained from MW could be solved through a reanalysis of previously reported experimental data. Two years later, the same kind of weighted‐least‐square fit of the existing experimental microwave data resulted in a new r 0 structure for vinyl fluoride (Smith, Coffey, & Radom, 1992). It must be indicated, however, that in some specific cases the MP2 method leads to unreliable geometries.…”
Section: Performance Of the Modelmentioning
confidence: 99%